The Concept of Moral Education in The Qur'an: A Comparative Study of Tafsir Ibn Katsir and Tafsir Fath Al-Qadir - Rizal, Muhammad; Sumarna, Lukman (CV. Publikasi Indonesia, 2025)
This study aims to analyze and compare the concept of moral education in the Qur'an through a comparative study between Tafsir Ibn Kathir and Tafsir Fath Al-Qadir by Imam Ash-Syaukani. The focus of the research is directed to five main verses, namely Surah An-Nisa' verse 36, Al-Hujurat verse 11-12, Al-Isra' verse 53, Al-Furqan verse 63, and Al-A'raf verse 199, which contain the fundamental values of moral education such as monotheism, doing good to parents, relatives, neighbors, peers, and prohibiting negative behavior such as arrogance, prejudice, and bullying. The method used is qualitative research with a library research approach. The results of the study show that the two interpretations have fundamental similarities in emphasizing the importance of moral education based on monotheism and the strengthening of universal moral values. However, there are differences in the methodological approach: Ibn Kathir's Tafsir prioritizes tafsir bi al-ma'tsur (history-based) and quotes a lot from hadith and the opinions of the Companions, while Tafsir Fath Al-Qadir combines the methods of history and ra'yi (rational-critical) with an emphasis on linguistic analysis and contextualization of moral values. These similarities and differences enrich perspectives in understanding the moral education of the Qur'an comprehensively and applicatively in the modern era. The suggestion of this study is for educators, policymakers, and the public to integrate the moral educational values of the Qur'an into the curriculum and practice of daily life by referring to the richness of classical and contextual interpretation. By understanding the depth of interpretation and its implications for moral education, it is hoped that a young generation can be formed with noble character, responsibility, and able to answer moral challenges in the current era.